Impact of CSR on Firm Value: The Moderating Role of Corporate Governance - Affaf Asghar Butt; Aamer Shahzad; Jamshaid Ahmad (Universitas Pasundan, 2020)
This study aims to investigate whether the corporate governance (CG) moderates the link between corporate social responsibility (CSR) and firm value (FV). For this purpose, anatomization was conducted by extracting data from the published annual reports of non-financial firms listed on the Pakistan Stock Exchange. Correlation, regression, and moderation analyses were conducted to obtain the statistical outcomes. The results showed a significant direct relationship between CSR and firm performance. Additionally, it was found that the interactivity between CSR and FV weakened when CG was included as a moderator. The results of this study could be used by stakeholders to make economically sound decisions since it provides complete guidance regarding how to engage in productive CSR activities. Moreover, this study contributes to future research by examining the association between CSR and FV using CG as a moderator, in a market where, as in other developing markets, this relationship has not been the focus of research. Apart from its theoretical contributions, this study explores the role of CG as moderator, in line with research conducted in under-developed markets, which may be considered a significant contribution.